Magnesium application partially reversed the negative effects of mulching on rhizosphere nitrogen cycling in a Phyllostachys praecox forest - Zhao, Hong; Kuang, Xiaobao; Li, Yi; Li, Tian; Wang, Tian; Yu, Lin; Xia, Congcong; Dong, Huanhuan; Shen, Jiacheng; Fu, Bojie; Zhou, Hanchang (Frontiers in Plant Science, 2025)
Mulching is the practice of covering soil with a layer of organic or inorganic material. While this process is often used in bamboo forests to increase yield, it has also been found to lead to bamboo degradation, especially in Phyllostachys praecox (Lei-bamboo) forests. Studies suggest that mulching might accelerate degradation by altering rhizosphere nitrogen cycling, a process likely influenced by the depletion of soil calcium and magnesium. However, the specific changes to rhizosphere nitrogen cycling under mulching and its relationship with calcium and magnesium remain unclear. To address this, our study investigated rhizosphere nitrogen cycling in Lei-bamboo across a short-term degradation cycle. We found that mulching enhanced the abundance of 16S-rRNA and nitrogen-cycling functional genes. Correspondingly, it also significantly enhanced soil respiration and nitrogen-cycling functional potentials, leading to ammonium accumulation but nitrate depletion. The rhizosphere nitrogen-cycling network reorganized as the relative contributions of gdhA, AOB-amoA, napA, nirK, and nosZ increased. Surprisingly, nitrite accumulated under mulching due to a decrease in the nxrA/AOB ratio. Although total organic carbon, total nitrogen, and pH were the main drivers of nitrogen cycling variation, magnesium also exerted considerable influence. Subsequent field amendment experiments confirmed that magnesium was the most limited nutrient under mulching. Magnesium supplementation further elevated rhizosphere microbial biomass and nitrogen-cycling functional potential, which calcium did not. The composition indicators of nitrogen-cycling groups, such as nxrA/AOB, as well as the content of ammonia and nitrite, reverted toward their original states after magnesium application, but the nitrate further reduced. Our findings suggest that magnesium application can partially counteract the negative effects of mulching on the rhizosphere nitrogen cycle. We discovered that nitrification processes and nxrA were more sensitive to magnesium than other nitrogen-cycling processes and functional genes, indicating they could be key sites where magnesium regulates nitrogen cycling. This research provides a new idea for the biogeochemical coupling of magnesium and nitrogen and offers useful guidance for sustainable mulching in Lei-bamboo agriculture.